2012
DOI: 10.1371/journal.pone.0052643
|View full text |Cite
|
Sign up to set email alerts
|

High Serum Carotenoids Associated with Lower Risk for Bone Loss and Osteoporosis in Post-Menopausal Japanese Female Subjects: Prospective Cohort Study

Abstract: IntroductionRecent epidemiological studies show that high intakes of carotenoids might be useful to maintain bone health, but little is known about the association of serum carotenoids with change of bone mineral density (BMD). The objective of this study was to investigate longitudinally whether serum carotenoids are associated with bone loss.MethodsWe conducted a follow-up on 146 male and 99 pre- and 212 post-menopausal female subjects from the Mikkabi study. Those who participated in previous BMD surveys an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
52
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(59 citation statements)
references
References 34 publications
4
52
1
Order By: Relevance
“…9) In OVX mice, the administration of lutein partly restored the bone loss due to estrogen deficiency (data not shown), but further studies are needed to define the possible role of lutein in the prevention of postmenopausal osteoporosis. Sugiura et al 17,18) reported that the intake of a Japanese citrus containing β-cryptoxanthin was related to bone density in postmenopausal women. Lutein is synthesized and accumulated in green leafy plants such as spinach and kale.…”
Section: Discussionmentioning
confidence: 99%
“…9) In OVX mice, the administration of lutein partly restored the bone loss due to estrogen deficiency (data not shown), but further studies are needed to define the possible role of lutein in the prevention of postmenopausal osteoporosis. Sugiura et al 17,18) reported that the intake of a Japanese citrus containing β-cryptoxanthin was related to bone density in postmenopausal women. Lutein is synthesized and accumulated in green leafy plants such as spinach and kale.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a high dose of retinol will increase the risk of hip fracture. Sugiura and colleagues reported that people with high serum beta‐carotene had less developed osteoporosis than those with a low level of serum beta‐carotene. In their study, osteoporosis was defined as a person whose T ‐score (which shows how a subject's BMD compares with the young adult mean) is less than 70%, according to the guidelines on the management of osteoporosis by the Japan Osteoporosis Society .…”
Section: Discussionmentioning
confidence: 99%
“…(28) Thus, a high dose of retinol will increase the risk of hip fracture. Sugiura and colleagues (29) reported that people with Fig. 2.…”
Section: Discussionmentioning
confidence: 99%
“…Ishimi et al (1999) reported that physiological concentrations of carotenoids may induce positive bone turnover by inhibiting osteoclast formation in vitro. Moreover, several recent epidemiological reports have shown an inverse association between carotenoid intake or serum level with low BMD, risk of fracture and/or risk of osteoporosis (Sahni et al, 2009a;Sugiura et al, 2012). In addition, kiwifruit contains polyphenols such as catechin and chlorogenic acid.…”
Section: Discussionmentioning
confidence: 99%